1986
DOI: 10.1095/biolreprod35.2.267
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Estradiol, Testosterone, and Progesterone Levels during the Ovulatory Cycle of the Skate (Raja Erinacea)1

Abstract: Amounts of estradiol, testosterone, and progesterone in plasma were measured during the reproductive cycle of female Raja erinacea. Estradiol titers correlated directly with follicle size in females undergoing ovarian recrudescence, while highest concentrations were found in females with preovulatory follicles. These data indicate that as follicles grow, their steroidogenic capacity increases. In mature, nonspawning females, titers of estradiol and testosterone varied markedly. Progesterone was not detected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 25 publications
6
51
0
Order By: Relevance
“…Over the last decade there has been an increased understanding of the reproductive endocrinology of chondrichthyans (Koob et al 1986, Koob & Callard 1999, Gelsleichter 2004, Sulikowski et al 2005. Only a few studies have compared the levels of plasma steroid hormones between juvenile and adult chondrichthyans, and all of these suggest that hormones could be used as an indicator of maturational status (Rasmussen & Gruber 1990, 1993, Rasmussen & Murru 1992, Gelsleichter et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade there has been an increased understanding of the reproductive endocrinology of chondrichthyans (Koob et al 1986, Koob & Callard 1999, Gelsleichter 2004, Sulikowski et al 2005. Only a few studies have compared the levels of plasma steroid hormones between juvenile and adult chondrichthyans, and all of these suggest that hormones could be used as an indicator of maturational status (Rasmussen & Gruber 1990, 1993, Rasmussen & Murru 1992, Gelsleichter et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…A significant difference in the observance of both non-gravid and gravid mature females by month was observed, with a higher frequency of mature non-gravid females in May, October and November, and a higher frequency of mature gravid females in October and December these hormones are associated with follicular growth leading to ovulation (Koob & Callard 1999, Awruch 2013. Although the role that testosterone plays in viviparous elasmobranchs remains unclear (Awruch 2013), previous research suggests that this hormone is a substrate for estradiol biosynthesis (Tsang & Callard 1982) and is correlated with follicular development (Koob et al 1986). Given this, our findings suggest that the collective estradiol and testosterone concentrations can be used as a predictor of gravidity in sharks 300 cm TL and larger.…”
Section: Discussionmentioning
confidence: 51%
“…Additionally, there does not appear to be any seasonal pattern to the proportion of resting B. interrupta females, as found for Alantoraja cyclophora (Oddone and Vooren 2005). Koob et al (1986) suggested that Raja erinacea, which reproduces year round, undergoes cyclic (though not necessarily synchronised) periods of reproductive inactivity and ovarian recrudescence between spawning periods. If skates have inconsistent periods of reproductive resting, this would be important to account for when quantifying lifetime fecundity for demography and fisheries management purposes.…”
Section: Reproductive Resting Stagementioning
confidence: 87%